Planting Rights Liberalization in the European Union: An Analysis of the Possible Effects on the Wine Sector in Rheinland-Pfalz, Germany - Mariia Bogonos; Barbara Engler; Jur̈gen Oberhofer; Marc Dreßler; Stephan Dabbert (German Journal of Agricultural Economics (GJAE), 2016)
This study investigates the effects of planting rights liberalization on the largest wine-producing region in Germany, Rheinland-Pfalz. Introduced by the reform of the Common Agricultural Policy (CAP) of the European Union (EU) in 2008, the abolishment of restrictions on the planting of new vineyards is still a subject of controversial discussions regarding possible effects on the sector's structure and the quantity of wine production. For a simulation of these effects, this study uses partial equilibrium modeling and Markov chain projection. The results reveal that the effects of abolishment of planting rights depend on the assumed wine must prices. Relatively high market prices for wine must would lead to increases in the production of both standard and basic quality wine must and in the number of more cost-effective wine farms in the region. If low prices for wine must are assumed, the reform might result only in minor impacts.
Keywords: 330